Efficient cycloisomerization of propargyl amides by electrophilic gold(I) complexes of KITPHOS monophosphines: a comparative study - Doherty, Simon; Knight, Julian G.; Hashmi, A. Stephen K.; Smyth, Catherine H.; Ward, Nicholas A. B.; Robson, Katharine J.; Tweedley, Sophie; Harrington, Ross W.; Clegg, William (Organometallics, 2010)
Electrophilic gold(I) complexes of diphenyl- and dicyclohexylphosphino-based KITPHOS monophosphines catalyze the 5-exo-dig cycloisomerization of a range of propargyl amides to afford the corresponding alkylidene oxazolines; in all cases catalysts formed from diphenylphosphino-substituted KITPHOS monophosphines outperformed their dicyclohexylphosphino counterparts as well as that based on triphenylphosphine, an indication that the biaryl/biaryl-like framework may be responsible for imparting high catalyst efficiency.
Gesehen am 16.02.2023